Respon Pertumbuhan Dan Hasil Tanaman Kacang Tanah (Arachis hypogeae L.) Terhadap Pemberian Pupuk Kalium Dan Sistem Olah Tanah - Darmi, Darmi; Syahrani, Syahrani (Jurnal Magrobis, 2013)
Response on Growth and Yield of Peanut (Arachis Hypogeae L.) by Potassium Fertilizing and Soil Tillage System.The purpose of the study was to determine the effect of the interaction between potassium fertilizer application and soil tillage systems on the growth and yield of peanuts and getting potassium fertilizer and tillage systems optimum for the growth and yield of peanut.The experiment was conducted approximately four (4) months since September 2012 until December 2012 starting from land preparation to harvest. The research was located in the Ponoragan village of Loa Kulu Sub District of Kutai Kartanegara Regency in East Kalimantan Province.Randomized Completely Block Design (RCBD) was used as factorial experimental design with three times replication. The first factor was Potassium Fertilizer with four levels, i.e. k0 = 0 kg K2O ha-1 ; k1= 30 kg K2O ha-1 equal with 32 g KCl plot-1 ; k2 = 60 kg K2O ha-1 equal with 63 g KCl plot-1 and k3 = 90 kg K2O ha-1 equal with 95 g KCl plot-1. Whilst the second factor was soil tillage system with three levels, i.e. s0 = no tillage ; s1 = minimum tillage and s2 = maximum tillage (intensively tillage).The results showed that application of potassium fertilizer was significantly affected to height of plant, number of pods per plant, number of void pods per plant, weight of seed per plant, number of dry seed per plant and production of dry seed. The highest of dry seed production was reached at k3 = 90 kg K2O ha-1equal with 95 g KCl plot-1 with average 1.61t ha-1.The results also showed that soil tillage system was significantly affected to height of plant, number of pods per plant, number of void pods per plant, weight of seed per plant, number of dry seed per plant and production of dry seed. The highest of dry seed production was reached at s2 = maximum tillage (intensively tillage) with average 1.78t ha-1.Interaction between application of potassium fertilizer and soil tillage system was not affected to all parameters observed.Keyword : Peanut, Potassium Fertilizing, Soil Tillage System